Application of Bio-Electrical Instruments for Monitoring the Effect of Muscle Massage on Post-Stroke Patients Through Electromyography Signal Measurement - Triwiyanto Triwiyanto; Torib Hamzah; Sari Luthfiyah; Bedjo Utomo; Urip Mudjiono (Forum Ilmiah Teknologi dan Ilmu Kesehatan (FORITIKES), 2022)
The problems faced by partners are: in carrying out traditional massage massage practice activities, partners do not carry out the process of recording medical conditions before or after the massage process. Thus, this causes partners to be unable to remember the conditions before and after the provision of traditional massage therapy. In addition, when giving traditional massage to patients who have to return periodically, partners cannot know the impact after giving traditional massage. So, to know the result is to ask questions to the patient (e.g.